Desenvolvimento de um bobinador microcontrolado para indutores e transformadores de alta frequência - Urbanski, Lucas Muriana (2017)
This work of Conclusion of Course has the objective of developing a microcontrolled coil winding machine for inductors and transformers of high frequency, realizing the autonomous winding of the spirals in a core of the type E. Laboratory and prototyping practices commonly use critical components such as inductor, for example, which require values of inductance not commercially produced, therefore, the manual development of the component is necessary. In this context, a system that can automate this manual process could be of great value, using microcontrolled circuits to carry out the winding process, the risk of component failure is minimized. A system was then developed that automates the winding process using step motors controlled by a microcontroller.